The Effect of Corporate Tax Avoidance on the Cost of Equity - Goh, Beng Wee; Lee, Jimmy; Lim, Chee Yeow; Shevlin, Terry (The Accounting Review, 2016)
ABSTRACT Based on Lambert, Leuz, and Verrecchia's (2007) derivation of the cost of equity capital in terms of expected cash flows, we generate a testable hypothesis that relates tax avoidance to a firm's cost of equity capital. Using three broad measures of tax avoidance—book-tax differences, permanent book-tax differences, and long-run cash effective tax rates—to test our hypothesis, we find that the cost of equity is lower for tax-avoiding firms. This effect is stronger for firms with better outside monitoring, firms that likely realize higher marginal benefits from tax savings, and firms with higher information quality. Overall, our results suggest that equity investors generally require a lower expected rate of return due to the positive cash flow effects of corporate tax avoidance. JEL Classifications: G32; H26; M41.